Prevalence And Epidemiological Determinants of Malnutrition Among Under-Fives in An Urban Slum, Nagpur - Dhatrak, Poonam P; Pitale, Smita; Kasturwar, N B; Nayse, Jaydeep; Relwani, Nisha (National Journal of Community Medicine, 2013)
Background: The prevalence of malnutrition among preschool children can be used to determine the need for nutritional surveillance, nutritional care, or appropriate nutritional intervention programmes in a community. Objectives: To study prevalence of stunting, wasting and underweight in under fives and to find out epidemiological determinants associated with malnutrition. Methodology: A community based cross-sectional study was carried out to assess prevalence of stunting, wasting, underweight and epidemiological determinants associated with malnutrition among under-fives in the field practice area of Urban health training centre (UHTC), dept. of Community Medicine, NKP Salve Institute of Medical Sciences and Research Centre, Nagpur. Data was collected by predesigned, pre-tested questionnaires. Data analysis was done by using Epi Info software. Results: Out of the total 150 children 46% were underweight, 52% were stunted and 20.7% were wasted. The total prevalence of malnutrition was 63.33%. The factors associated with malnutrition were low birth weight (85%), mothers literacy (77.78%), fathers literacy (73.97), lack of exclusive breast feeding (81.25%), socio-economic-status (74.44%) and incomplete immunization (76.19%). Conclusion: The study strongly points toward the importance of proper infant feeding practises, proper nutrition, parental education and improved living conditions for reducing malnutrition among under-five children.